Economic Features of the Use of Electric Vehicles in Delivery Services in Estonia - Prokopenko, Olha; Järvis, Marina; Prause, Gunnar; Kara, Inna; Kyrychenko, Hanna; Kochubei, Oleksandr; Prokopenko, Maryna (International Journal of Energy Economics and Policy, 2022)
The article is devoted to substantiating the prospects and advantages of developing a small business specializing in the delivery of lightweight cargo in Tallinn during the Covid-19 pandemic. It was justified why such a business should not only be cost effective but also comply with the general principles of sustainable development and be socially responsible. Particular attention in the article is paid to identifying possible alternative strategies for forming the vehicle park of such a company. Analytically (based on the latest data from the auto producer; car, energy and fuel markets, as well as a company specializing in the construction of turnkey solar power plants), it has been proven that a mixed park, which is consists of gasoline cars and plug-in hybrids is the most a flexible solution requiring an investment exclusively in moving property. At the same time, it was shown that if a company has territorial capabilities to accommodate a sufficient number of solar panels and is ready to organize a business with a smaller park of cars, then the choice of electric ones becomes obvious.